2005
DOI: 10.1002/art.21122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of doxycycline on progression of osteoarthritis: Results of a randomized, placebo‐controlled, double‐blind trial

Abstract: Objective. To confirm preclinical data suggesting that doxycycline can slow the progression of osteoarthritis (OA). The primary outcome measure was joint space narrowing (JSN) in the medial tibiofemoral compartment.Methods. In this placebo-controlled trial, obese women (n ‫؍‬ 431) ages 45-64 years with unilateral radiographic knee OA were randomly assigned to receive 30 months of treatment with 100 mg doxycycline or placebo twice a day. Tibiofemoral JSN was measured manually in fluoroscopically standardized ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
202
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(218 citation statements)
references
References 34 publications
13
202
0
3
Order By: Relevance
“…The experimental dog model of ACLT-induced OA has been used extensively for such purposes (20,21,23,(25)(26)(27) and could thus be an exception and serve as a useful tool in the study of human OA. Studies have recently shown that the positive effects of doxycycline on OA structural changes in an experimental dog model of OA (28) could also be seen in patients with knee OA treated with this drug (29). These findings are interesting, but before any final judgment can be made, the results need to be further validated by confirmatory studies.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental dog model of ACLT-induced OA has been used extensively for such purposes (20,21,23,(25)(26)(27) and could thus be an exception and serve as a useful tool in the study of human OA. Studies have recently shown that the positive effects of doxycycline on OA structural changes in an experimental dog model of OA (28) could also be seen in patients with knee OA treated with this drug (29). These findings are interesting, but before any final judgment can be made, the results need to be further validated by confirmatory studies.…”
Section: Discussionmentioning
confidence: 98%
“…It has a long-term record of relative safety and few recognized adverse effects, namely sun sensitivity, monilial vaginitis, and nonspecific gastrointestinal symptoms. In a human trial that used doxycycline for 30 months, only these three side effects were observed (Brandt et al, 2005). No serious adverse events, such as death, hospitalization, and development of a life-threatening or debilitating condition, were attributable to doxycycline.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of hyaluronan on prevention of OA seems to be limited according to several metaanalyses. 17 Recently, novel approaches such as injection of caspase inhibitors, 18 treatment with basic fibroblast growth factor, 19 oral doxycycline, 20 and oral glucosamine 21 have been reported for OA prevention. In our results, BMP-7 reduced OA progression but did not block progression of OA completely.…”
Section: Discussionmentioning
confidence: 99%